“I Don’t Think I Have an Attention Span for Real Life Anymore”: Excessive Stimulation, Sense of Meaninglessness, and Boredom in Sam Levinson’s Euphoria - Anna Pochmara (European Journal of American Studies)
The article analyzes selected episodes from the HBO teen drama Euphoria (2019–) and argues that it both reproduces and comments on the boredom of satiety. Directed by Sam Levinson, the show has been repeatedly praised for its dynamic aesthetic. The swirling kaleidoscope of scenes and images in Euphoria mimics the contemporary immersion in social media and digital representations. The frenetic visual pace of the show’s regular episodes, however, is broken with slow-paced and seemingly boring special episodes. Yet, I will show that their focus on in-person, engaged conversations is a refreshing break from the boredom of satiety and serves as an antidote to the loss of meaningfulness experienced by the teenage protagonists.